Analisis Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5 (Studi Kasus: STIKES Garuda Putih Jambi) - Samsinar Samsinar; Rudolf Sinaga; Renny Afriany (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The implementation of IT requires good IT governance mechanisms to conduct comprehensive oversight so that the business goals of an organization can truly be achieved effectively and efficiently. All levels of IT managers must understand that risk is uncertain and harms a goal to be achieved. Risk can be a big challenge for any organization or institution that must be able to perform risk management as best it can. With well-managed risk management, it will be able to protect IT assets and add value to IT management. STIKES Garuda Putih is one of the nonprofit organizations that operate in the field of health education. To ensure excellent service for all communities and stakeholders related to IT services, it is necessary to conduct IT governance analysis activities to see if it is working properly. The analysis activity will be done using the COBIT framework 5. In this study, the capability model as a measuring tool for respondents' answers from the questionnaire is made based on the cobit framework 5. Based on the results of the process maturity level analysis on IT management (capability) is in the 3.6 to 1.4 the gap, so that concluded that IT governance has been implemented, but there is still the domain must be improved to achieve the maximum level. It is recommended that SOPs and IT performance management achievement reports, IT risk management, IT management strategy improvement, and the need for an internal control structure of IT governance be established